Pengaruh Kualitas Produk, Harga, Dan Pengalaman Pelanggan Terhadap Kepuasan Pelanggan Di SOS Sushi On The Street Badung - Patrick Pascalino Suwandhi; Luh Komang Candra Dewi; I Putu Agus Suarsana Ariesta (Journal Research of Management, 2025)
In recent years, Japanese food has become one of the growing trends in Bali. Japanese restaurants offer a variety of Japanese cuisine, and also present an authentic gastronomic experience for local and tourist visitors. This study aims to analyze the effect of Product Quality, Price and Customer Experience on Customer Satisfaction at Sushi on The Street Badung. This study applies a quantitative descriptive research method. The Sampling Determination Technique used in this study is the purposive sampling research method. The research analysis uses multiple regression analysis. The sample in this study is consumers or customers of SOS Sushi on The Street Badung who are 17 years old and over who are considered capable of providing information in accordance with the existing facts. The results of the study indicate that 1. Product Quality (X1) has a positive and significant effect on Customer Satisfaction (Y) SOS Sushi on The Street Badung, 2. Price (X2) has a positive and significant effect on Customer Satisfaction (Y) SOS Sushi on The Street Badung, 3. Customer Experience (X2) has a positive and significant effect on Customer Satisfaction (Y) SOS Sushi on The Street Badung and 4. The most dominant independent variable influencing customer satisfaction at SOS Sushi on The Street is Product Quality (X1)